RISIKO PRODUKSI USAHATANI PADI MODEL CORPORATE FARMING DI JAWA TENGAH - Muhammad Joni Iskandar; Rini Endang Prasetyowati; Muhammad Anwar (Universitas Sebelas Maret, 2024)
Corporate farming is a strategic step to increase the production and productivity of subsistence lowland rice farming. In addition, the use of corporate farming model agriculture is a new opportunity to overcome the risk of national rice production. Especially at this time, the rice fields are getting narrower due to the conversion of functions into agro-tourism, housing, industry, and services. The purpose of this research is to estimate the production risk and farmers' behavior towards the risk of rice farming with the corporate farming model in Sukoharjo Regency, Central Java. The result of this research shows that the risk of production of the corporate farming model is high with a variability of 50.45. This means that the corporate farming model of rice farming faces the risk of major crop failure. Factors that influence the increase in production risk are SP-36 fertilizer and pesticides, while land area, Urea fertilizer, NPK fertilizer, and labor have the potential to reduce production risk but have no significant effect. Farmers' behavior towards the risk of farming with the corporate farming model is risk aversion. The attitude of reluctant farmers is shown by their behavior in facing the intermediate risk of 32 farmers